1992
DOI: 10.1111/j.1476-5381.1992.tb14398.x
|View full text |Cite
|
Sign up to set email alerts
|

An endothelial 5‐HT receptor that mediates relaxation in guinea‐pig isolated jugular vein resembles the 5‐HT1D subtype

Abstract: 1 Endothelium-dependent and -independent, concentration-related, relaxations to 5-hydroxytryptamine (5-HT) are described in a preparation of guinea-pig isolated jugular vein. 2 An endothelial 5-HT receptor was studied in the presence of mesulergine (at 10.0 JLM, a concentration sufficient to antagonize 5-HT2 receptor-mediated contractions and endothelium-independent relaxations to 5-HT). Relaxations mediated by the endothelial 5-HT receptor were resistant to antagonism by 5 Both 5-HT and sumatriptan evoked end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…The endothelial location of the receptor could not be con®rmed by experiments in which the endothelium is removed as previous experience dictates that any attempt to remove the endothelium greatly damages the thin and fragile underlying smooth muscle in this preparation. Endothelial, vasodilator 5-HT receptors have previously been identi®ed in arteries and veins as being similar to either the 5-HT 2B subtype or the 5-HT 1D/1B subtype Gupta, 1992;Glusa Roos, 1996). In the present study, in the 4-day-old rabbit vessels, GR55562 inhibited 5-CT-induced vasodilation suggesting that the 5-HT 1B/1D subtype mediated NO-dependent vasodilation in these vessels.…”
Section: -Ht Receptor-induced Vasodilationsupporting
confidence: 49%
See 1 more Smart Citation
“…The endothelial location of the receptor could not be con®rmed by experiments in which the endothelium is removed as previous experience dictates that any attempt to remove the endothelium greatly damages the thin and fragile underlying smooth muscle in this preparation. Endothelial, vasodilator 5-HT receptors have previously been identi®ed in arteries and veins as being similar to either the 5-HT 2B subtype or the 5-HT 1D/1B subtype Gupta, 1992;Glusa Roos, 1996). In the present study, in the 4-day-old rabbit vessels, GR55562 inhibited 5-CT-induced vasodilation suggesting that the 5-HT 1B/1D subtype mediated NO-dependent vasodilation in these vessels.…”
Section: -Ht Receptor-induced Vasodilationsupporting
confidence: 49%
“…In other vascular beds, 5-HT can induce endothelium-dependent vasodilation via the 5-HT 2C receptor (Bodelson et al, 1993), the 5-HT 2B receptor (Glusa & Roos, 1996;Ellis et al, 1995) and the 5-HT 1D/1B receptor (Gupta, 1992). There is also evidence that 5-HT can mediate vasodilation directly through 5-HT 4 and 5-HT 7 receptors located on vascular smooth muscle (Cocks & Arnold, 1992;Leung et al, 1996;Terron, 1996).…”
Section: Introductionmentioning
confidence: 98%
“…Whilst some have been classified as 5-HT,-like (Schoeffter & Hoyer, 1990;Gupta, 1992), others may be tentatively classified as subtypes of the 5-HT2 receptor family. Thus, endothelial 5-HT receptors mediating relaxation of rabbit jugular vein (Leff et al, 1987), rat jugular vein (Bodelsson et al, 1992), piglet vena cava (Sumner, 1991) and pig pulmonary artery (Glusa, 1992) share some pharmacological identity with both 5-HT2B (Wainscott et al, 1993) and 5-HT2C (Hoyer et al, 1989) receptors.…”
Section: Introduction Methodsmentioning
confidence: 99%
“…However, the 5-HT receptor which mediates this response is atypical and pharmacologically distinct from the vascular smooth muscle 5-HTI-like receptor subtypes Sumner, 1991). Of greater interest is the observation that both sumatriptan and 5-carboxamidotryptamine can elicit endothelial-dependent relaxation responses in the pig isolated coronary artery (Molderings et al, 1989;Schoeffter & Hoyer, 1990) and guinea-pig isolated jugular vein (Gupta, 1992). This suggests that the endothelial cells in some blood vessels may also possess a 5-HTI-like receptor with a pharmacological profile which is actually consistent with the vasoconstrictor subtype found on the vascular smooth muscle (for further discussion see Cambridge et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in specific isolated blood vessels (Molderings et al, 1989;Schoeffter & Hoyer, 1990;Gupta, 1992) in vitro indicated that sumatriptan and 5-carboxamidotryptamine could elicit endothelial-dependent relaxation through the relese of nitric oxide (NO), the endothelial-derived vasodilator formerly known as EDRF (Khan & Furchgott, 1987;Ignarro et al, 1987;Palmer et al, 1987 (Whiting & Cambridge, 1991) (Green, 1979). …”
Section: Introductionmentioning
confidence: 99%